1999
DOI: 10.2165/00003088-199936040-00004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Potential Interactions Amongst Antiretroviral Agents Used To Treat Patients with HIV Infection

Abstract: There are 3 groups of drugs available for the treatment of patients with HIV disease. These are the nucleoside reverse transcriptase inhibitors ('nucleoside analogues') [zidovudine, didanosine, zalcitabine, lamivudine and abacavir]; the non-nucleoside reverse transcriptase inhibitors (nevirapine, delavirdine and efavirenz); and the protease inhibitors (saquinavir, ritonavir, indinavir, nelfinavir and amprenavir). The preferred initial regimen should reduce and maintain plasma HIV RNA below the level of detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
168
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(175 citation statements)
references
References 60 publications
3
168
1
3
Order By: Relevance
“…Consistent with these in vivo studies, ABT-378, NFV, RTV, and SQV, but not APV or IDV, increased TG synthesis and RTV increased CH synthesis in HepG2 cells. These and other observations 1,7,[12][13][14]20,21 indicate that select PIs affect multiple, distinct metabolic pathways, perhaps accounting for the different side effects observed for each PI in the clinic. This may be due to differences in affinity for cellular proteins (eg, proteases), cell permeability, tissue distribution, or metabolism of PI.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Consistent with these in vivo studies, ABT-378, NFV, RTV, and SQV, but not APV or IDV, increased TG synthesis and RTV increased CH synthesis in HepG2 cells. These and other observations 1,7,[12][13][14]20,21 indicate that select PIs affect multiple, distinct metabolic pathways, perhaps accounting for the different side effects observed for each PI in the clinic. This may be due to differences in affinity for cellular proteins (eg, proteases), cell permeability, tissue distribution, or metabolism of PI.…”
Section: Discussionmentioning
confidence: 78%
“…N ucleoside reverse transcriptase inhibitors (NRTIs), 1 nonnucleoside reverse transcriptase inhibitors (NNRTIs), and HIV protease inhibitors (PIs) are 3 classes of antiretroviral drugs that are used in the treatment of patients with AIDS. NRTIs and NNRTIs inhibit HIV reverse transcriptase and suppress replication of the virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of compartmental pharmacokinetic analysis for examining efavirenz disposition in ACTG 5043 yielded estimates and comparisons of pharmacokinetic microconstants that would not have been identified with standard non-compartmental analysis. The rationale for our modeling approach relates to known characteristics of efavirenz that include, ~50% bioavailability [12,13] and oxidative metabolism via CYP3A and CYP2B6 to inactive hydroxylated metabolites including 8-and 7-hydroxyefavirenz, with subsequent urinary and biliary excretion after glucuronidation in the liver [3,14,15]. In a previous investigation, nevirapine, an inducer of CYP2B6 and CYP3A4, significantly decreased the plasma concentrations of efavirenz, indicating that either CYP2B6 or CYP3A4 or both contribute to the biotransformation of efavirenz [16].…”
Section: Discussionmentioning
confidence: 99%
“…Computerized systems can support electronic prescribing; however, a systematic review of such systems showed that 55-91.2% of drug interaction alerts are ignored by physicians [26,27].…”
Section: Discussionmentioning
confidence: 99%